Synthesis and Characterization of New Phthalimides Containing 1, 2, 4-triazole and Imine Group - Ali, Khalid F.; Hussain, Eman M.; Ahmed, Rana S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Several new derivatives of 1, 2, 4-triazoles linked to phthalimide moiety were synthesized through following multisteps. The first step involved preparation of 2, 2-diphthalimidyl ethanoic acid [2] via reaction of two moles of phthalimide with dichloroacetic acid. Treatment of the resulted imide with ethanol in the second step afforded 2,2-diphthalimidyl ester[3] which inturn was introduced in reaction with hydrazine hydrate in the third step ,producing the corresponding hydrazide derivative[4] .The synthesized hydazide  was introduced in different synthetic paths including treatment with carbon disulfide in alkaline solution then with hydrazine hydrate to afford the new 1,2,4-triazole[10] .Reaction of compound [10] with different aldehydes produced a new Schiff base derivatives[11,12] .Reaction of derivative [4] with different aldehydes produced a new derivatives [5-8].All the synthesized compounds have been characterized by melting points ,FTIR ,1HNMR(some of them ) and mass spectroscopy of compound [2]. Derivatives [5, 6, 7, 10, 11, 12] were tested against inhibition of E-coli, staphyloccus aureus  and were all  found  to be active. Schem1,2 illustrated the reaction steps.